Innovation as a lever for sustainable development - Zilli, Sandro (Community Notebook. People, Education and Welfare in the Society 5.0, 2021)
We are living through an unprecedented time in history, characterised by the speed and unpredictability with which changes occur. On the other hand, it is also a time to seize the opportunity to realise what is expressed in the UN Sustainable Development Goals 2030, namely: building a resilient infrastructure and promoting innovation and fair, responsible and sustainable industrialisation. Innovation is one of the determining factors for achieving sustainable development that cannot disregard the ethical principle of co-responsibility, i.e. a fundamental assumption that leads to an integral ecological vision based on the centrality of the person. These principles are the levers with which to support and strengthen the capacity of countries to increase productivity and incomes, as well as to foster better outcomes in essential services such as health and education.